Analysis Of Zhondang Pan and Gerald M. Kosicki's Framing Model on Tvri's Political News Broadcast Program 'South Sulawesi Today - Amalia, Ayu; Yusmanizar, Yusmanizar; Sukmarini, Andi Vita (Journal La Sociale, 2024)
This study aims to analyse the framing of political news presented by the South Sulawesi Hari Ini news broadcast program on TVRI South Sulawesi. The focus of the study is directed at three main problem formulations: (1) identifying framing elements contained in political news, (2) revealing framing techniques used in framing political issues, and (3) evaluating the extent to which the construction of political news fulfils the function of the media as a means of informative and educational information, a means of political socialization, and a tool for public oversight. The analysis method used is the Pan and Kosicki framing model, which examines the syntactic, script, thematic, and rhetorical structures in news texts. The research findings show that TVRI South Sulawesi compiles political news with a neutral, formal, and public service-oriented approach. The discourse structure is arranged to clarify the political process procedurally, without presenting biased opinions or excessive emotional effects. The framing techniques used tend to be informative and educational, supporting the role of public media as a balancer of information in the midst of a competitive and often sensational media landscape. Thus, the framing applied in political news on TVRI South Sulawesi can be said to be in line with the principles of public journalism: objective, balanced, and prioritizing the interests of the community.